2015
DOI: 10.1108/ijlma-12-2014-0063
|View full text |Cite
|
Sign up to set email alerts
|

Does country-level governance enhance ethical behaviour of firms? An African perspective

Abstract: Purpose – The purpose of this paper is to examine the relationship between country-level governance and ethical behaviour of firms in African countries in the period 2009-2012. Design/methodology/approach – It uses a broad set of country-level governance ratings by the World Bank and data on ethical behaviour of firms by the World Economic Forum’s report on Global Competitiveness. Full data of a total of 39 African economies out of the 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…Similarly, different studies reported a positive link between regulatory quality and entrepreneurship aspects (e.g. Cule & Fulton, 2013;Avram et al, 2015;Chambers & Munemo, 2017;Agyemang et al, 2015;Kamarudin et al, 2016;Tong et al, 2018;Montinola & Jackman, 2002;Treisman, 2000). In the same context, Chambers and Munemo (2017) suggest that the level of entrepreneurship is highly determined by a country's regulatory and institutional environment.…”
Section: Political Stability Absence Of Violence and Entrepreneurshipmentioning
confidence: 92%
See 4 more Smart Citations
“…Similarly, different studies reported a positive link between regulatory quality and entrepreneurship aspects (e.g. Cule & Fulton, 2013;Avram et al, 2015;Chambers & Munemo, 2017;Agyemang et al, 2015;Kamarudin et al, 2016;Tong et al, 2018;Montinola & Jackman, 2002;Treisman, 2000). In the same context, Chambers and Munemo (2017) suggest that the level of entrepreneurship is highly determined by a country's regulatory and institutional environment.…”
Section: Political Stability Absence Of Violence and Entrepreneurshipmentioning
confidence: 92%
“…Several studies have reported a link between rule of law and entrepreneurship (e.g. Shagbazian & Aistov, 2017;Ngunjiri, 2010;Haggard & Haggard, 2018;Agyemang et al, 2015;Kamarudin et al, 2016;Saona, 2016;Tong et al, 2018;Goltz et al, 2015). The literature review establishes a piece of evidence on the negative effect of regulations (Djankov et al, 2002;Klapper et al, 2006).…”
Section: Rule Of Law and Entrepreneurshipmentioning
confidence: 97%
See 3 more Smart Citations